Comparative toxicity assessment of selected nanoparticles using different experimental model organisms. - Parashar, S.; Raj, S.; Srivastava, P.; Singh, A.K. (Journal of pharmacological and toxicological methods, 2024)
Nanoparticles are microscopic particles ranging in size from one to one hundred nanometers. Due to their extensive features, nanoparticles find widespread use in various fields worldwide, including cosmetics, medical diagnosis, pharmaceuticals, food products, drug delivery, electronic devices, artificial implants, and skincare. However, their unique characteristics have led to high demand and large-scale manufacturing, resulting in adverse impacts on the environment and bioaccumulation. Researchers have been exploring issues related to the environmental toxicity resulting from the high production of selected nanoparticles. This review discusses and addresses the adverse impacts of highly produced nanoparticles such as Carbon Nanotubes, Silica, Titanium dioxide, Zinc Oxide, Copper oxide, and Silver nanoparticles on different in vivo, in vitro, alternate invertebrate models, and plant models. Summarizing in vivo research on rats, rabbits, and earthworms, the review reveals that nanoparticles induce cytotoxicity, embryotoxicity, and DNA damage, primarily targeting organs like the brain, liver, kidney, and lungs, leading to nephron, neuro, and hepatotoxicity. Studying the effects on alternative models like zebrafish, Caenorhabditis elegans, Drosophila, sea urchins, and Saccharomyces cerevisiae demonstrates genotoxicity, apoptosis, and cell damage, affecting reproduction, locomotion, and behavior. Additionally, research on various cell lines such as HepG2, BALB/c 3 T3, and NCL-H292 during in vitro studies reveals apoptosis, increased production of reactive oxygen species (ROS), halted cell growth, and reduced cell metabolism. The review highlights the potentially adverse impacts of nanoparticles on the environment and living organisms if not used sustainably and with caution. The widespread use of nanoparticles poses hazards to both the environment and human health, necessitating appropriate actions and measures for their beneficial use. Therefore, this review focuses on widely used nanoparticles like zinc, titanium, copper, silica, carbon nanotubes, and silver, chosen due to their environmental toxicity when excessively used. Environmental toxicity of air, water, and soil is evaluated using environmentally relevant alternative animal models such as Drosophila, zebrafish, earthworms, etc., alongside in vivo and in vitro models, as depicted in the graphical abstract.